1996
DOI: 10.1046/j.1525-1438.1996.06050356.x
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy for advanced ovarian cancer

Abstract: Neoadjuvant chemotherapy with cisplatin or carboplatin was administered to 29 patients with advanced ovarian carcinoma prior to their undergoing definitive cytoreductive surgery. Twenty‐eight patients had ascites, eight had pleural effusion, and 16 had extensive upper abdominal disease on computerized tomography scan. The CA125 response to neoadjuvant chemotherapy was highly predictive of survival (P<0.0005). A 2‐log decrease in CA125 prior to surgery resulted in a median survival of 37 months, while patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 10 publications
4
62
1
5
Order By: Relevance
“…Neoadjuvant chemotherapy decreases tumor volume and facilitates surgical procedures especially chemosensitive tumor which had completed or partial clinical response achievement in 76% of patients with less residual volume which had an impact of decrease morbidity and mortality and improving clinical outcome [16]- [23]. Analysis of our data showed significant improvement in both progression-free survival and overall survival in those underwent NACT-IDS compared to PDS-ACTR these results comparable to those published by Kuhn et al [24] [25], Rose et al, and Muggia et al [6] [24] [25] [26], they showed prolonged survival times and significantly better median survival in NACT group than the conventional PDS-ACTR. According to data published by Onnis et al [18] and Surwit et al…”
Section: A H Zaky Et Alsupporting
confidence: 86%
“…Neoadjuvant chemotherapy decreases tumor volume and facilitates surgical procedures especially chemosensitive tumor which had completed or partial clinical response achievement in 76% of patients with less residual volume which had an impact of decrease morbidity and mortality and improving clinical outcome [16]- [23]. Analysis of our data showed significant improvement in both progression-free survival and overall survival in those underwent NACT-IDS compared to PDS-ACTR these results comparable to those published by Kuhn et al [24] [25], Rose et al, and Muggia et al [6] [24] [25] [26], they showed prolonged survival times and significantly better median survival in NACT group than the conventional PDS-ACTR. According to data published by Onnis et al [18] and Surwit et al…”
Section: A H Zaky Et Alsupporting
confidence: 86%
“…Jacob et al reported optimal cytoreduction in 77% of patients, 7 and Surwit et al reported 55% of cytoreduction to less than 1 cm. 8 However, in our opinion, the potential benefit of neoadjuvant chemotherapy does not lie in an increasing rate of optimal cytoreduction, because trained teams report high levels of optimal cytoreduction with initial aggressive debulking (87% for Heintz et al, 17 85.2% of total macroscopic disease removal for Eisenkop et al 18 However, the optimal cytoreduction rate must not be considered separately from the morbidity of debulking surgery and the subsequent quality of life. The value of neoadjuvant chemotherapy is to obtain optimal cytoreduction by means of less aggressive surgery that we believe is associated with less morbidity.…”
Section: Discussionmentioning
confidence: 89%
“…Previous published series concerning neoadjuvant chemotherapy for advanced ovarian carcinoma included some patients with medical contraindications to surgery, 6 or who were referred after inadequate surgery, 7 or whose disease was nonsurgically staged. 8,9 Because it has been clearly established that primary debulking surgery is beneficial when the residual tumor is less than 2 cm, 5 we wanted to select for neoadjuvant chemotherapy only those patients for whom this goal seemed unfeasible by means of surgery associated with acceptable morbidity, i.e., standard surgery. 10 However, few patients meet all of these selection criteria, because pelvic lesions are almost always debulkable by extraperitoneal dissection, as described by Hudson,11 and the limits of standard debulking surgery are extended bowel involvement, large involvement of the peritoneum located in the upper abdomen, particularly in the dorsal diaphragmatic area, and liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy for two or three cycles may reduce disease burden and increase tumor resectability while simultaneously allowing performance status to improve. Surgery after neoadjuvant chemotherapy is associated with less intraoperative blood loss, shorter operative times, fewer intensive care unit admissions, and a shorter duration of hospital stay [60,61].…”
Section: Interval Debulkingmentioning
confidence: 99%